Automated Infusion Monitoring Device Using Arduino-Based IoT (Internet of Things) - Wijayanto, Budi; Hermawan, Andi; Marlinda, Linda (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Efforts to improve healthcare services in the medical world are being made by implementing rapidly evolving Computer and Information Technology. In the medical field, particularly in infusion procedures, this is the most commonly used device. The function of infusion is to administer fluids or medication into the body through an intravenous route at a constant rate for a specific period. Infusion is performed for patients who urgently need medication or require a continuous and slow administration of fluids due to dehydration. However, during implementation in the field, issues may arise due to a lack of medical personnel and nursing errors, especially considering the ongoing Covid-19 conditions. An automated infusion monitoring device is one of the solutions created to ease the nursing process by monitoring and regulating the infusion flow rate through a monitor that displays real-time fluid volume in the nurse's area. The author employs an Arduino Mega 2560 as the data reader, a Load Cell sensor to measure the weight of the fluid in the infusion, a Servo to control the infusion flow rate, and an ESP module to connect to the server